Conflictual Diversity and Contested Cultural Heritage: Newspaper Coverage of Religion in Norway 1938-2018 - Lundby, Knut (Temenos, 2019)
The visibility and diversity of religion in selected Norwegian newspapers published in the capital of Oslo is studied in a quantitative analysis at ten-year intervals from 1938 to 2018, with an emphasis on the last forty years. Recent structural transformations in the newspaper industry and editorial choices cut the number of articles on religion considerably in 2018 compared to earlier years. However, the relative visibility of religion in the share of the total editorial output is fairly stable, at about 1.5 per cent of the content. Rather, the changes have been with the diversity and criticism of religion. The representation of Islam has strongly increased, while the newspapers have played down the coverage of the Lutheran majority church. The conflictual diversity and contested cultural heritage in the newspaper material arepartly shaped by the media dynamics in the mediatization of religion.